2012
DOI: 10.1002/emmm.201200243
|View full text |Cite
|
Sign up to set email alerts
|

Modification of γ‐secretase by nitrosative stress links neuronal ageing to sporadic Alzheimer's disease

Abstract: Inherited familial Alzheimer’s disease (AD) is characterized by small increases in the ratio of Aβ42 versus Aβ40 peptide which is thought to drive the amyloid plaque formation in the brain of these patients. Little is known however whether ageing, the major risk factor for sporadic AD, affects amyloid beta-peptide (Aβ) generation as well. Here we demonstrate that the secretion of Aβ is enhanced in an in vitro model of neuronal ageing, correlating with an increase in γ-secretase complex formation. Moreover we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 57 publications
7
53
0
Order By: Relevance
“…There are two main reasons to believe that nitro-oxidative stress is an etiopathogenic factor in AD (Dawson and Dawson, 1996;Smith et al, 1997;Miranda et al, 2000;Tamagno et al, 2002;Coma et al, 2008;Guix et al, 2009). First, aging is the major risk factor for AD and is associated with an unbalanced redox state due to the failure of antioxidant mechanisms (Hensley et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main reasons to believe that nitro-oxidative stress is an etiopathogenic factor in AD (Dawson and Dawson, 1996;Smith et al, 1997;Miranda et al, 2000;Tamagno et al, 2002;Coma et al, 2008;Guix et al, 2009). First, aging is the major risk factor for AD and is associated with an unbalanced redox state due to the failure of antioxidant mechanisms (Hensley et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Protein nitration is an irreversible, post-translational modification that adds a nitro group to an amino acid, but mainly to a tyrosine, giving 3-nitrotyrosine residues (Guix et al, 2005); increased levels of protein nitration exist in AD (Smith et al, 1997). Numerous proteins have been reported to be affected by amyloid-dependent nitrotyrosination, thus severely affecting their function: presenilins (Guix et al, 2012), albumin , and the glycolytic enzymes triosephosphate isomerase (Guix et A␤ has one tyrosine (Y10) in its sequence, which is surrounded by negatively charged amino acids, making protein nitration very likely (Guix et al, 2005). Accordingly, Kummer et al (2011) reported increased levels of nitrotyrosinated A␤ and its presence in the core of amyloid plaques in AD brains.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nitrosative stress caused by peroxynitrite has a critical role in the etiology and pathogenesis of AD. [2][3][4][5][6][7] Peroxynitrite is implicated in the formation of the two hallmarks of AD, Ab aggregates and neurofibrillary tangles containing hyperphosphorylated Tau protein. 1,4,7 In addition, peroxynitrite promotes the nitrotyrosination of presenilin 1, the catalytic subunit of the g-secretase complex, which shifts production of Ab to amyloid beta (Ab)42 and increases the Ab42/Ab40 ratio, ultimately resulting in an increased propensity for aggregation and neurotoxicity.…”
mentioning
confidence: 99%
“…1,4,7 In addition, peroxynitrite promotes the nitrotyrosination of presenilin 1, the catalytic subunit of the g-secretase complex, which shifts production of Ab to amyloid beta (Ab)42 and increases the Ab42/Ab40 ratio, ultimately resulting in an increased propensity for aggregation and neurotoxicity. 5 Furthermore, nitration of Ab tyrosine 10 enhances its aggregation. 6 Peroxynitrite can also modify enzymes, such as triosephosphate isomerase, 4 and activate kinases, including Jun amino-terminal kinase and p38 mitogen-activated protein kinase, which enhance neuronal cell death.…”
mentioning
confidence: 99%
“…ADF / Cofilin Family of Proteins with Alzheimer's Disease. Unlocking if cofilin1's inactive is a cause or consequence of AD pathology requiring further investigation [22]. We found that both in vivo and in vitro a significant increase in the ratio of pcofilin1 / cofilin1 indicates that cofilin1 is inactivated in the brain of AD patients and APP / PS1 mice as a result of AD pathology (Fig.…”
Section: Function Of Adf/cofilin Family Proteins In Central Nervous Smentioning
confidence: 79%